Celastrol attenuates Alzheimer’s disease-mediated learning and memory impairment by inhibiting endoplasmic reticulum stress-induced inflammation and oxidative stress - Fanfan Cao; Limin Xu; Xiaoxue He; Yongbin Chi; Ying Wang; Qiuyun Liu; Denghai Zhang (Archives of Medical Science)
Introduction Alzheimer’s disease (AD) is triggered by biological mechanisms such as neuroinflammation and oxidative stress. Endoplasmic reticulum (ER) stress can lead to the expression of molecular chaperones in the ER, which helps in restoring cellular homeostasis. Researchers have highlighted the role of ER stress in the progression of AD, suggesting that regulating it could be a potential treatment strategy for AD.